Harmonic elimination by SPWM and THIPWM techniques applied in photovoltaic inverters - Falil Fatima; Bénabadji Nourddine (International Journal of Applied Power Engineering (IJAPE), 2021)
With advances in solid-state power electronic devices, control techniques (PWM) have been devised to obtain high dynamics responses from a multilevel power conditioning converter-Photovoltaic. This work discusses the advantages and drawbacks of two different PWM techniques, the sinusoidal (SPWM) technique and the Third harmonic injection PWM (THIPWM) technique. These two methods are compared by discussing their ease of implementation and by analyzing the output harmonic spectra of various output voltage and their total harmonic distortion (THD). The focus of this paper is the simulation study of single-phase inverter, three phases, two levels and three levels inverter for application photovoltaic. Firstly, single phase is modeled with inductive load and their waveforms are observed. Secondly, a two levels inverter, and three levels inverter are leading to the high industrial performances of the drives synchronous, especially, if a high-power quality is requested.